PERBEDAAN TINGKAT PERTUMBUHAN PENDAPATAN NASIONAL LAJU INFLASI, TINGKAT SUKU BUNGA INDONESIA DAN AMERIKA KAITANNYA TERHADAP NILAI TUKAR RUPIAH DENGAN DOLLAR AMERIKA PERIODE 2000-2007 - Musdholifah, ; Humam Kurdiya Gunadi, (Pendidikan Ekonomi, 2012)
Since the employment of the floating currency system, the movement of Rupiah currency is determined by the market mechanism, or in other words, the fluctuation of currency depends on the supply and demand in money market. The study uses multiple linier regression analysis, in which the independent variables are the difference of national income growth level(X1), difference of inflation rate  (X2), difference of interest rate  (X3) in Indonesia and United States of America, while the dependent variable is the fluctuation of Rupiah against US dollar (Y), and another independent variable is the prior currency  (t-1) (X4). The result of the study indicates that (X1), (X2), (X3) do  not have significant influence on the fluctuation of Rupiah against UD dollar, while (X4) does. To sum up, in addition to macroeconomic factors, non economic ones also influence the fluctuation of Rupiah against US dollar.